Preparation method of lanthanum-promoted sulfydryl acid silicon-based catalyst
By promoting the preparation and application of thiolic acid silicon-based catalysts by lanthanum, the problems of low catalyst selectivity, low acetone conversion rate and large three-waste production in the traditional bisphenol A production process are solved, and efficient, environmentally friendly and economical bisphenol A production is achieved.
Patent Information
- Application Number
- CN202411495422.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-11
AI Technical Summary
The traditional bisphenol A production process has problems such as low catalyst selectivity, low acetone conversion rate, large three-waste production, high equipment requirements and high cost.
A highly efficient solid acid catalyst is prepared by a combination of polyether, ethyl orthosilicate, hydrogen peroxide, 3-mercaptopropyl and lanthanum nitrate. The catalyst reacts with phenol and acetone at room temperature to achieve efficient synthesis of bisphenol A by gradient heating.
The conversion rate of acetone has been significantly improved to about 90%, the total yield of bisphenol A has been improved to about 96%, the generation of by-products has been reduced, the purity of the product has been improved, the generation of three wastes has been reduced, and the production cost and environmental pressure have been reduced.
Smart Images

Figure CN119588416A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic chemistry, and more specifically, particularly relates to a method for preparing a lanthanum-promoted mercapto acid silicon-based catalyst. Background Art
[0002] As an important industrial compound, bisphenol A is widely used in many fields. However, its traditional production process has many problems and challenges.
[0003] In the traditional production process of bisphenol A, sulfuric acid, hydrochloric acid, etc. are usually used as catalysts, or cation exchange resins, etc. are used for catalytic reaction. The sulfuric acid method has few equipment and simple process, but many by-products are generated when synthesizing bisphenol A, the product quality is poor, the material consumption quota is high, the labor intensity is high, and a large amount of three wastes that are difficult to handle are generated. Although the hydrochloric acid method has better product quality, the process flow is long, the equipment investment is large, the reaction time is long, acidic wastewater is generated, the equipment is susceptible to corrosion, and the energy consumption and investment are high. Although the ion exchange resin method is non-corrosive, less polluting, the catalyst is easy to separate, the product quality is high, and the operation is simple, the catalyst is expensive, the raw material phenol has high requirements, and the acetone per-pass conversion rate is low, and an acetone recovery device needs to be equipped.
[0004] The catalysts used in traditional processes have many defects, such as large amounts of three wastes generated, high treatment costs, high equipment and energy requirements, expensive one-time use of catalysts and difficulty in recycling, low selectivity leading to low acetone conversion, etc. These problems not only increase production costs and reduce production efficiency, but also put great pressure on the environment.
[0005] Therefore, in order to solve the problems existing in the traditional production process of bisphenol A, it is particularly important to develop a new, efficient, environmentally friendly and economical catalyst preparation method. The lanthanum-promoted mercapto acid silicon-based catalyst preparation method of the present invention came into being under such a background, aiming to overcome the shortcomings of the traditional process and provide a better solution for the production of bisphenol A. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a lanthanum-promoted mercapto acid silicon-based catalyst to solve the above problems.
[0007] The method for preparing a lanthanum-promoted mercapto acid silicon-based catalyst comprises the following steps: Step 1: Dissolve 4 g of polyether (P123) in 125 ml of 1.9 mol / L hydrochloric acid at room temperature; Step 2: Heat the solution to 40°C, add 7.8 g of ethyl orthosilicate, stir vigorously for 45 min, add 0.86 g of hydrogen peroxide, 0.1 g of 3-mercaptopropyl and 1.62 g of lanthanum nitrate, and stir for 6 h; Step 3: Dry in an oven at 110°C for 24 hours to obtain a catalyst.
[0008] Preferably, the molar ratio of hydrogen peroxide to 3-mercaptopropyl group, the molar ratio of ethyl orthosilicate to 3-mercaptopropyl group, and the molar ratio of lanthanum nitrate to 3-mercaptopropyl group are all 9 / 1.
[0009] A method for synthesizing bisphenol A using the lanthanum-promoted mercapto acid silicon-based catalyst prepared by the above method comprises the following steps: Add 10 g of phenol, 2.5 g of acetone, 1.5 g of the catalyst and a magnet to a three-necked flask in sequence, ensure airtightness, stir, increase the temperature gradually from 0 to 75° C., react for 6 h, and stop heating and stirring.
[0010] Preferably, after the reaction is completed, the three-necked flask is replaced with a room temperature electromagnetic stirring heating jacket, stirred, and (cold) deionized water is slowly poured into the reaction system.
[0011] Preferably, stirring is continued for 30 minutes after the deionized water is added.
[0012] Preferably, suction filtration is performed after stirring is completed.
[0013] Preferably, after filtration, the solution is rinsed with deionized water to a pH of 7.
[0014] Preferably, after rinsing, the crude bisphenol A is dried in an oven at 65°C.
[0015] Preferably, after drying, the crude product is dissolved in 15 ml of toluene, mixed evenly and then placed in ice-salt water for water separation and recrystallization is stopped when a large amount of white needle-shaped crystals are precipitated.
[0016] Preferably, after the recrystallization is completed, the white needle-shaped crystals are dried in an oven at 65° C. and then bottled.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The lanthanum-promoted mercapto acid silicon-based catalyst of the present invention significantly improves the conversion rate of acetone, which can reach about 90%. Compared with the traditional process (such as 82-85% of the sulfuric acid method and about 50% of the ion exchange resin method), the waste of raw materials is greatly reduced, the reaction efficiency is improved, and the output of bisphenol A is increased. The total yield of bisphenol A is as high as about 96%, which is higher than the traditional process (82-85% of the sulfuric acid method, about 95% of the hydrochloric acid method, and about 91% of the ion exchange resin method), thereby improving the production efficiency.
[0018] 2. This catalyst is a solid acid catalyst, which is stable in the condensation reaction system. It can be separated from the bisphenol A product by filtration and can be reused. Traditional liquid acid catalysts are difficult to recycle. The mercapto acid group is used as the acid activation center, which improves the selectivity of the synthesis of bisphenol A, reduces the formation of by-products, and improves the purity of the product.
[0019] 3. The catalyst can be reused, which reduces the investment cost of the catalyst, has low equipment requirements, reduces equipment investment and maintenance costs, reduces dependence on expensive raw materials (such as cation exchange resins in traditional ion exchange resin methods), and reduces raw material costs.
[0020] 4. Very little three wastes are generated during the synthesis process, especially the generation of acidic wastewater is greatly reduced, which reduces environmental pressure, reduces the generation of by-products, reduces waste emissions, and is beneficial to environmental protection.
[0021] 5. The synthesis process of the catalyst is simple and easy to operate and control. The synthesis reaction conditions of bisphenol A are mild and easy to achieve and regulate. The synthesized bisphenol A has the appearance of white needle-shaped crystals with a purity of more than 98%. The product quality is better than bisphenol A synthesized by traditional processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a data table of 5 parallel experiments conducted in the present invention to verify the stability and repeatability of the preparation process; Figure 2 is a data table diagram of 5 parallel experiments conducted in the present invention to evaluate the effect of the method for synthesizing bisphenol A of the present invention; Figure 3 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION
[0023] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0024] As an important industrial compound, bisphenol A has a wide range of applications in many fields. However, the traditional bisphenol A production process has many problems, such as low catalyst selectivity, low acetone conversion rate, large amount of three wastes generated, high equipment requirements and high cost. The lanthanum-promoted mercapto acid silicon-based catalyst preparation method proposed in the present invention aims to solve these problems and provide an efficient, environmentally friendly and economical bisphenol A production method. The specific implementation method of the method will be introduced in detail below, and its advantages and innovations will be demonstrated by comparison with the traditional process.
[0025] 1. Preparation of lanthanum-promoted mercapto acid silicon-based catalysts: Experimental Materials: Polyether (P123): chemically pure, molecular weight about 5800; 1.9 mol / L hydrochloric acid: analytical grade, prepared by diluting concentrated hydrochloric acid; Ethyl orthosilicate: analytical grade, purity ≥98%; 3-Mercaptopropyl (trimethoxysilane): analytical grade, purity ≥97%; Hydrogen peroxide: analytical grade, mass fraction about 30%; Lanthanum nitrate: analytical grade, purity ≥99%.
[0026] Experimental equipment: Electronic balance: precision 0.01g, used to accurately weigh various reagents; Constant temperature water bath: temperature control accuracy ±0.5℃, providing stable reaction temperature; Magnetic stirrer: speed range 0-1500 rpm, to ensure uniform mixing of the reaction system; Oven: temperature control range 0-200℃, used for drying reaction products.
[0027] Preparation steps: In a fume hood, use an electronic balance to weigh 4 g of polyether (P123) and carefully pour it into a 250 ml glass beaker. Then use a measuring cylinder to measure 125 ml of 1.9 mol / L hydrochloric acid and slowly add it to the beaker containing polyether (P123). Use a magnetic stirrer to stir at room temperature (about 25°C) until the solution becomes clear and transparent. The stirring speed is set to 500 rpm and the stirring time is about 30 minutes. Transfer the clear solution to a thermostatic water bath and set the temperature to 40°C. After the temperature stabilizes, use a pipette to accurately measure 7.8 g of ethyl orthosilicate and slowly add it dropwise to the suspension. While adding ethyl orthosilicate, start the magnetic stirrer at the same time, increase the stirring speed to 800 rpm, and continue to stir vigorously for 45 minutes to ensure adequate mixing; According to the pre-calculated molar ratio (ethyl orthosilicate / 3-mercaptopropyl = 9 / 1; hydrogen peroxide / 3-mercaptopropyl = 9 / 1; lanthanum nitrate / 3-mercaptopropyl = 9 / 1), use an electronic balance to weigh 0.86g of hydrogen peroxide, 0.1g of 3-mercaptopropyl and 1.62g of lanthanum nitrate respectively. First, add 0.1g of 3-mercaptopropyl to the above suspension and stir for 5 minutes to mix it evenly. Then slowly add 0.86g of hydrogen peroxide to the suspension and continue stirring for 10 minutes. Finally, carefully add 1.62g of lanthanum nitrate and continue stirring for 6 hours to allow the reaction to proceed fully; The reaction mixture was transferred to a clean ceramic tray and spread evenly. The tray was then placed in an oven and the temperature was set to 110°C for drying. The drying time was 24 hours to ensure that the water was completely evaporated to obtain a solid lanthanum-promoted mercapto acid silicon-based catalyst.
[0028] In order to verify the stability and repeatability of the preparation process, 5 parallel experiments were conducted and the relevant data were recorded, as shown in the following table: .
[0029] By analyzing the above experimental data, it can be calculated that the average catalyst yield is about 10.3g. The relative standard deviation (RSD) is less than 2%, indicating that the preparation method has good repeatability and stability.
[0030] 2. Synthesis of Bisphenol A: Experimental Materials: Phenol: analytical grade, purity ≥99%; Acetone: analytical grade, purity ≥99.5%; The lanthanum-promoted mercapto acid silicon-based catalyst prepared above; Magnetic: used to stir the reaction system; Deionized water: resistivity ≥18.2MΩ・cm; Toluene: analytical grade, purity ≥99%.
[0031] Experimental equipment: Three-necked flask: 500 ml, equipped with thermometer, condenser and nitrogen inlet; Electromagnetic stirrer: adjustable stirring speed and temperature; Thermometer: range 0-150℃, accuracy 0.1℃; Filtration device: including Buchner funnel, filtration bottle, and vacuum pump; pH meter: accuracy 0.01; Oven: Same as the oven used in catalyst preparation.
[0032] Synthesis steps: In a clean and dry 500ml three-necked flask, use an electronic balance to accurately weigh 10g of phenol, 2.5g of acetone, 1.5g of the above-prepared lanthanum-promoted mercapto acid silicon-based catalyst and a magnet. Install the thermometer and condenser, and ensure that the three-necked flask is airtight. Then place the three-necked flask on an electromagnetic stirrer, turn on the stirring, and set the stirring speed to 600 rpm. Then, through program temperature control, gradually increase the temperature from room temperature (about 25°C) to 75°C at a heating rate of 10°C / hour, and maintain this temperature for 6 hours. After the reaction is completed, stop heating and stirring; After the reaction is completed, remove the three-necked flask from the heating device and quickly transfer it to an electromagnetic stirring heating jacket that is pre-set to room temperature (about 25°C). Keep the stirring state unchanged and use a constant pressure dropping funnel to slowly add (cold) deionized water to the reaction system. The dropping speed is controlled at 5ml / min, and the total dropping amount is about 50ml; After the addition is complete, continue stirring for 30 minutes to allow the reaction system to be fully mixed. The stirring speed is maintained at 400 rpm; After stirring, a suction filtration device was set up to filter the reaction mixture to separate the crude bisphenol A. A vacuum pump was used to maintain negative pressure during the filtration process, and the pressure was about -0.08 MPa; Rinse the crude bisphenol A product with deionized water several times until the pH of the rinse water reaches 7 when tested with a pH meter. The amount of water used for each rinse is about 30 ml; Transfer the rinsed crude bisphenol A to a clean tray and place it in a 65°C oven for drying. The drying time is about 4 hours to ensure that the moisture is completely removed; Take out the dried crude bisphenol A from the oven and transfer it to a 250 ml round-bottom flask. Use a measuring cylinder to measure 15 ml of toluene and add it to the round-bottom flask. Install the reflux condenser and stir on a magnetic stirrer to completely dissolve the crude bisphenol A. The stirring speed is 300 rpm and the stirring time is about 30 minutes; Transfer the dissolved solution to a large beaker and place it in the pre-prepared ice-salt water for water-reinforced recrystallization. When a large amount of white needle-like crystals are observed to precipitate, stop the recrystallization operation; The recrystallized white needle-shaped crystals were placed in an oven at 65°C for drying for 2 hours, and then placed in a dry sample bottle and sealed for storage.
[0033] Experimental data and analysis: In order to evaluate the effect of the method for synthesizing bisphenol A of the present invention, 5 parallel experiments were conducted and compared with the traditional processes (sulfuric acid method, hydrochloric acid method and ion exchange resin method). The data are shown in the following table: .
[0034] By comparison, it can be seen that the method of the present invention is significantly superior to the conventional process in terms of bisphenol A yield, acetone conversion rate and total yield. The average conversion rate of acetone in the method of the present invention is about 90.5%, while the average acetone conversion rate in the conventional sulfuric acid method is about 83.2%, in the conventional hydrochloric acid method is about 94.2%, and in the conventional ion exchange resin method is about 51.0%. In terms of total yield, the method of the present invention reaches an average of about 96.0%, while the conventional sulfuric acid method is 82.8%, the conventional hydrochloric acid method is about 95.0%, and the conventional ion exchange resin method is about 90.8%.
[0035] In addition, the quality of the synthesized bisphenol A products was tested, and the results are shown in the following table: .
[0036] The liquid acid catalyst used in the traditional sulfuric acid method and hydrochloric acid method is highly corrosive, which not only causes serious damage to the equipment, but is also difficult to recycle, resulting in increased production costs and environmental pollution. The lanthanum-promoted mercapto acid silicon-based catalyst of the present invention is a solid acid catalyst with stable properties, which can be separated from the product by simple suction filtration, is easy to recycle and reuse, reduces the catalyst cost, and reduces environmental pollution; The cation exchange resin catalyst used in the traditional ion exchange resin method is expensive and sensitive to impurities in the raw materials, requiring the purity of phenol to be high. However, the lanthanum-promoted mercapto acid silicon-based catalyst synthesis raw materials of the present invention are relatively cheap and easy to obtain, and the purity requirement for the raw material phenol is relatively low, further reducing the production cost; The reaction temperature of the traditional sulfuric acid method is usually controlled at 35-40°C, and the reaction time is 4-6 hours; the reaction temperature of the hydrochloric acid method is about 60-65°C, and the reaction time is several hours. In contrast, the reaction temperature range of the method of the present invention is wider, starting from room temperature and rising to 75°C in a gradient manner, and the reaction time is 6 hours. This flexible temperature control and moderate reaction time make the reaction process easier to operate and control, while improving production efficiency; Traditional processes have high requirements on the material and corrosion resistance of reaction equipment, and special alloys or glass-lined linings are required to resist acid corrosion. However, the lanthanum-promoted mercapto acid silicon-based catalyst used in the method of the present invention is mild in nature and less corrosive to equipment. Ordinary stainless steel equipment can meet the reaction requirements, greatly reducing equipment investment and maintenance costs; From the product appearance, the bisphenol A synthesized by the method of the present invention is pure white needle-shaped crystals, while the bisphenol A synthesized by the traditional process is often light yellow, indicating that the purity of the product obtained by the method of the present invention is higher. In terms of product selectivity, the traditional process is prone to produce a large number of by-products, such as o-bisphenol, o-p-bisphenol, triphenol, color and some other condensation products, due to the low selectivity of the catalyst. The lanthanum-promoted mercapto acid silicon-based catalyst of the present invention uses the mercapto acid group as the acidic activation center, which significantly improves the selectivity of synthesizing bisphenol A, reduces the generation of by-products, and thus improves the purity and yield of bisphenol A; The traditional sulfuric acid method and hydrochloric acid method will produce a large amount of acidic wastewater and waste gas during the reaction process, and the treatment of these three wastes requires high costs and complex treatment processes. The method of the present invention produces very little three wastes during the reaction process, and the acidity of the wastewater is low, which is easy to treat, greatly reducing environmental pressure and treatment costs. Although the traditional ion exchange resin method produces less wastewater, the resin needs to be regenerated or replaced after a certain period of use, which will also produce a certain amount of solid waste. The catalyst of the present invention has good stability and reusability, reducing the generation of solid waste; The lanthanum-promoted mercapto acid silicon-based catalyst preparation method of the present invention and its application in the synthesis of bisphenol A realize efficient, environmentally friendly and economical production of bisphenol A through carefully designed experimental steps and strictly controlled reaction conditions. Compared with the traditional process, the present invention shows significant advantages in catalyst performance, reaction conditions, product quality and selectivity, and three wastes discharge. Specifically, the catalyst of the present invention has the advantages of being recyclable and reusable, low corrosiveness and high selectivity; the reaction conditions are mild and easy to control; the product quality is high and the purity can reach more than 98.5%; the three wastes are generated in small amounts and are environmentally friendly. These advantages make the method of the present invention have broad application prospects and huge economic and social benefits in the industrial production of bisphenol A.
[0037] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
Claims
1. A method for preparing a lanthanum-promoted mercapto acid silicon-based catalyst, characterized in that: The following steps are involved: Step 1: Dissolve 4 g of polyether (P123) in 125 ml of 1.9 mol / L hydrochloric acid at room temperature; Step 2: Heat the solution to 40°C, add 7.8 g of ethyl orthosilicate, stir vigorously for 45 min, add 0.86 g of hydrogen peroxide, 0.1 g of 3-mercaptopropyl and 1.62 g of lanthanum nitrate, and stir for 6 h; Step 3: Dry in an oven at 110°C for 24 hours to obtain a catalyst.
2. A method for synthesizing bisphenol A using the lanthanum-promoted mercapto acid silicon-based catalyst prepared by the method of claim 1, characterized in that: The following steps are involved: Add 10 g of phenol, 2.5 g of acetone, 1.5 g of the catalyst and a magnet to a three-necked flask in sequence, ensure airtightness, stir, increase the temperature gradually from 0 to 75° C., react for 6 h, and stop heating and stirring.
3. The method for synthesizing bisphenol A according to claim 2, characterized in that: After the reaction was completed, the three-necked flask was replaced with a room temperature electromagnetic stirring heating jacket, stirred, and (cold) deionized water was slowly poured into the reaction system.
4. The method for synthesizing bisphenol A according to claim 3, characterized in that: After adding deionized water, continue stirring for 30 minutes.
5. The method for synthesizing bisphenol A according to claim 4, characterized in that: After stirring, filter by suction.
6. The method for synthesizing bisphenol A according to claim 5, characterized in that: After filtration, rinse with deionized water to pH = 7.
7. The method for synthesizing bisphenol A according to claim 6, characterized in that: After rinsing, the crude bisphenol A was dried in an oven at 65°C.
8. The method for synthesizing bisphenol A according to claim 7, characterized in that: After drying, dissolve the crude product in 15 ml of toluene, mix well and put it into ice-salt water for recrystallization. Stop when a large amount of white needle-like crystals precipitate.
9. The method for synthesizing bisphenol A according to claim 8, characterized in that: After recrystallization, the white needle-shaped crystals were dried in an oven at 65°C and then bottled.
10. The method for preparing the lanthanum-promoted mercapto acid silicon-based catalyst according to claim 1, characterized in that: The molar ratio of hydrogen peroxide to 3-mercaptopropyl group, the molar ratio of ethyl orthosilicate to 3-mercaptopropyl group, and the molar ratio of lanthanum nitrate to 3-mercaptopropyl group are all 9 / 1.